Filter design for satellite communications helical resonator technology - Doumanis, Efstratios; Goussetis, George; Kosmopoulos, Savvas (Artech House, 2015)
This new resource is a contemporary and comprehensive approach to the design of microwave filters with helical resonators. The very detailed step-by-step approach used throughout the book allows readers to quickly familiarize with the basic concepts of microwave filter design and confidently engage with the design of helical resonator filters.